Condução de calor envolvendo fonte móvel - Silveira, Sidney Ribeiro da (2015)
Problems involving heat conduction can be observed in many ways and in various forms, we can be mentioned: heating a slab in a welding process or heat conduction from a process of drilling or cutting. Thus, it is intended, using mathematical analysis tools and engineering concepts and physical establish this thermal behavior, by calculating 1D, 2D and 3D transient analytical solutions varying boundary conditions and apply it to a welding process. Obtaining analytical solutions to this problem require more elaborate procedures to those used for fixed problems because of the additional terms that arise in the governing equation. And so, we intend to contribute to the literature in this regard. The proposed method for solving partial differential equations will be the Green\'s functions method. It is also objective of this work to develop the verification of the solutions obtained analytically, making comparisons to the solutions obtained numerically and application in inverse problems. In this case, it is proposed to application and development of the TFBGF technique for heat source estimate. The use of analytical solution showed up after calculated and checks, a robust tool, easy to implement, and low computational cost when applied to direct or inverse problems of heat conduction by moving sources.